Data from: Evaluating the influence of different aspects of habitat fragmentation on mating patterns and pollen dispersal in the bird-pollinated Banksia sphaerocarpa var. caesia - Llorens, Tanya M.; Byrne, Margaret; Yates, Colin J.; Nistelberger, Heidi M.; Coates, David J. (Dryad, 2011)
Habitat fragmentation can significantly affect mating and pollen dispersal
patterns in plant populations, although the differential effects of the
various aspects of fragmentation are poorly understood. In this study we
used paternity assignment with eight microsatellite loci to investigate
the effect of fragmentation on the mating system and pollen dispersal
within one large and eight small population remnants of Banksia
sphaerocarpa var. caesia, a bird-pollinated shrub in the southern
agricultural region of Western Australia. The large population had a much
larger neighbourhood size and lower selfing rate, maternal pollen pool
differentiation and within-plot mean pollen dispersal distance than the
small populations. Outcrossing was consistently high and ranged from 89% ±
0.8 to 98.5% ± 0.3, and mating patterns suggested nearest-neighbour
pollination. Pollen immigration into small populations ranged from 6% ±
0.6 to 15% ± 0.6. Using the small populations, we tested for correlations
between various fragmentation variables and mating system and pollen
dispersal parameters. We found significant positive linear relationships
between population size and number of different fathers per seed crop and
between population shape and pollen pool differentiation. There were
significant negative linear relationships between population isolation and
outcrossing rate; population shape and neighbourhood size; and conspecific
density and mean pollen dispersal distance. Our results suggest that birds
may use a series of fragmented populations as a vegetation corridor while
foraging across the landscape and that population connectivity is a
critical determinant of pollinator visitation. Our results also suggest
that the effect of a linear population shape on the mating system and
pollen dispersal is routinely underestimated.
Adult genotypes and coordinatesMicrosatellite data for adult plants used
in the analyses. Adults were sampled from 9 populations. For 87F, all
adults within a focus area were sampled. For the remaining 8 populations,
all adults present within the population remnant were sampled. Columns are
as follows: ID of adult plants; Population code; Data for 8 microsatellite
loci; Geographic coordinates for each plant. Missing data are coded by
'0'. Geographic coordinates are latitude and longitude recorded
in decimal degrees using a differential GPS. Datum: Geocentric Datum of
Australia 1994 (GDA94). Data were collected by Tanya Llorens and Heidi
Nistelberger. Queries should be directed to Tanya Llorens.Progeny and
maternal genotypesMicrosatellite data for seedlings and mothers used in
the analyses. Seedlings were produced by germinating seeds collected from
maternal plants in nine populations. Columns are as follows: ID of
individual seedlings and maternal plants; ID of the mother of each
seedling; Population code; Data for 8 microsatellite loci. Missing data
are coded by '0'. For each seedling cohort, the rows of seedling
data are preceded by a row containing the maternal genotype. Data were
collected by Tanya Llorens and Heidi Nistelberger. Queries should be
directed to Tanya Llorens.
Keywords: Banksia sphaerocarpa var. caesia; pollen dispersal; population shape